Perioperative Nutrition in Pediatric Surgical Patients - Hasina, Kaniz; Enayet, SM Sabbir; Hanif, Abdul (Journal of Paediatric Surgeons of Bangladesh, 2016)
Abstract not available J. Paediatr. Surg. Bangladesh 5(2): 64-67, 2014 (July)